Analysis Of Risk Factors For Filariasis Incidence In North Sumatra Province (Data Analysis of Riskesdas 2018) - Rani Elviyanti Siregar; Putra Apriadi Siregar; Azhari Akmal Tarigan (International Archives of Medical Sciences and Public Health, 2021)
A North Sumatra Province is still one of the filariasis endemic areas with the number of cases recorded during 2012-2017 as many as 152 cases were converted at 1.10 per 100,000 population. This study aims to determine the risk factors for filariasis in North Sumatra Province. This study uses a quantitative approach with a cross-sectional study design. The type of data in this study is secondary data for Basic Health Research (Riskesdas) 2018 in January-August 2021. The number of samples in this study has gone through the data cleaning process and obtained as many as 59,210 samples. This data analysis technique used descriptive univariate analysis. The results obtained from the incidence of filariasis in North Sumatra Province as many as 623 (1.1%), with the age of the majority of respondents >24 years as many as 35,265 (59.6%), the majority being female as many as 30,499 (51.5%), the majority being education in the low category was 39,984 (67.5%), working status was 35,776 (60.4%), the majority lived in rural areas as much as 33,117 (55.9%), the majority used mosquito nets as much as 36,167 (61.1%), the majority of respondents did not use Reppelent 30,414 (51.4%), the majority of respondents did not install mosquito netting as many as 49,712 (84.0%), the majority of respondents did not consume filariasis prevention drugs as many as 51. 389 (86.8%) with the incidence of filariasis. It is hoped that the North Sumatra Provincial Health Office will coordinate with the district/city health offices in North Sumatra Province to maximize the consumption of filariasis drugs